2022
DOI: 10.1002/wps.20994
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in people with schizophrenia: a systematic review and meta‐analysis of relative risk and aggravating or attenuating factors

Abstract: People with schizophrenia die 15‐20 years prematurely. Understanding mortality risk and aggravating/attenuating factors is essential to reduce this gap. We conducted a systematic review and random‐effects meta‐analysis of prospective and retrospective, nationwide and targeted cohort studies assessing mortality risk in people with schizophrenia versus the general population or groups matched for physical comorbidities or groups with different psychiatric disorders, also assessing moderators. Primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
169
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 255 publications
(227 citation statements)
references
References 200 publications
(212 reference statements)
5
169
1
3
Order By: Relevance
“…[3][4][5] Despite the relatively low prevalence, schizophrenia is associated with substantial health, societal, and economic burden, including high healthcare resource utilization [6][7][8] and increased risk of premature mortality, disability, mental health comorbidities, and suicide. [9][10][11][12][13][14][15] Furthermore, the difficult symptoms associated with schizophrenia profoundly decrease patients' quality of life and daily functioning. 16,17 As a result of confirmed cases of illness caused by a SARS-CoV-2 Novel Coronavirus (2019-nCoV or COVID- 19), the US Secretary of Health and Human Services determined the existence of a public health emergency on January 27, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Despite the relatively low prevalence, schizophrenia is associated with substantial health, societal, and economic burden, including high healthcare resource utilization [6][7][8] and increased risk of premature mortality, disability, mental health comorbidities, and suicide. [9][10][11][12][13][14][15] Furthermore, the difficult symptoms associated with schizophrenia profoundly decrease patients' quality of life and daily functioning. 16,17 As a result of confirmed cases of illness caused by a SARS-CoV-2 Novel Coronavirus (2019-nCoV or COVID- 19), the US Secretary of Health and Human Services determined the existence of a public health emergency on January 27, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…There are eight items in the NOS, and the items are categorized into three dimensions, including selection, comparability, and outcomes. Studies were evaluated based on an NOS score from 0 to 9, with a score greater than 7 indicating high quality, a score between 5 and 6 indicating moderate quality, and one less than 5 indicating low quality [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…The concomitant comorbidity with other mental disorders determines the higher rates in symptomatology relapse, hospitalizations, suicidality, and family and social issues (such as higher rates of incarceration due to mental disorder relapse, treatment discontinuation, higher impulsivity and violent behaviors, and so forth), as well as a higher risk of negative outcomes in the short-term, including higher mortality rates [ 15 , 16 ]. A very recent meta-analysis showed that all causes of mortality were increased in people with schizophrenia, compared to the control group [ 17 ]. The specific causes of mortality included suicide, injury, poisoning, pulmonary diseases, endocrine diseases, respiratory diseases, urogenital diseases, diabetes, cancer, and cardio-cerebrovascular causes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…A very recent meta-analysis showed that all causes of mortality were increased in people with schizophrenia, compared to the control group [ 17 ]. The specific causes of mortality included suicide, injury, poisoning, pulmonary diseases, endocrine diseases, respiratory diseases, urogenital diseases, diabetes, cancer, and cardio-cerebrovascular causes [ 17 ]. Moreover, it has also been found that treatment with an antipsychotic (AP) drug, in particular with second-generation long-acting injectable antipsychotics (SGA-LAIs), seems to be protective against all causes of mortality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%